2015
DOI: 10.1111/1758-2229.12285
|View full text |Cite
|
Sign up to set email alerts
|

Early‐life establishment of the swine gut microbiome and impact on host phenotypes

Abstract: Early bacterial colonization and succession within the gastrointestinal tract has been suggested to be crucial in the establishment of specific microbiota composition and the shaping of host phenotype. Here, the composition and dynamics of faecal microbiomes were studied for 31 healthy piglets across five age strata (days 14, 36, 48, 60 and 70 after birth) together with their mothers. Faecal microbiome composition was assessed by 16S rRNA gene 454-pyrosequencing. Bacteroidetes and Firmicutes were the predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

68
371
7
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(448 citation statements)
references
References 72 publications
68
371
7
2
Order By: Relevance
“…Differences within the intestinal microbiota have explained variability in body weight in pigs; for example, at the phylum level, Firmicutes and Planctomycetes have been found at higher relative abundance in heavier pigs, while Bacteroidetes were more abundant in lighter pigs (21). In the same study, body weight-associated differences were found at the genus level (21), and a study by Mach et al showed that Prevotella was positively correlated with body weight (22). Intestinal microbiota composition has also been shown to vary between lean and obese pigs, with an increased abundance of Firmicutes found in obese pigs (15).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Differences within the intestinal microbiota have explained variability in body weight in pigs; for example, at the phylum level, Firmicutes and Planctomycetes have been found at higher relative abundance in heavier pigs, while Bacteroidetes were more abundant in lighter pigs (21). In the same study, body weight-associated differences were found at the genus level (21), and a study by Mach et al showed that Prevotella was positively correlated with body weight (22). Intestinal microbiota composition has also been shown to vary between lean and obese pigs, with an increased abundance of Firmicutes found in obese pigs (15).…”
mentioning
confidence: 79%
“…The advent of high-throughput sequencing has facilitated comprehensive profiling of the resident bacteria in the digestive tracts of pigs (17,22,29,30). However, this study is one of the first to exploit this technology to examine the intestinal microbiota among pigs of varying FE.…”
Section: Discussionmentioning
confidence: 99%
“…In the most reductionist version of the experiment, colonization of true germ-free pigs recapitulates postnatal development of the mucosal immune system (Laycock et al 2012). In 70-day-old Large White pigs with more complex, naturally establishing microbiomes, the presence of 'enterotypes' characterised by Ruminococcus or Prevotella was associated with differences in luminal secretory IgA concentrations, as well as body weight (Mach et al 2015), higher IgA levels and growth performances being seen in pigs with the Prevotella-dominated microbiomes. In this report, there was no antagonism between IgA levels expected to be protective and production traits.…”
Section: The Link Between the Intestinal Microbiota And The Mucosal Imentioning
confidence: 96%
“…The key role of intestinal Gram-positive bacteria in controlling adaptive immunity after respiratory infection with influenza virus has been recently highlighted in mice [36], demonstrating that all commensal bacteria did not contribute equally to the immunocompetence in the respiratory tract. In pigs, Lactobacillus genus exhibits a significant decline at weaning [37]. A direct intake of scFOS that is widely known to increase lactobacilli in vivo [38,39] may prevent this post-weaning decrease and subsequently improve the efficiency of the immune response to vaccination.…”
Section: Supplementation Of Piglets With Scfos Modulates Immune Responsementioning
confidence: 99%